Students' Acceptance of ChatGPT Technology: A Study of Its Positive and Negative Impacts on Academic Ethics and Learning Performance - Abdulhajar Encik; Wahyusari Ahada; Nevrita Nevrita; Irawan Dody; Zaitun Zaitun; Sartika Delita; Hasyim Taufiqurrahman (SHS Web of Conferences)
Artificial intelligence (AI) technology has had a major impact on education, making learning more interactive and efficient. ChatGPT, as an implementation of AI, allows students to get information quickly, but there are still challenges related to digital literacy and understanding academic ethics. Many students and educators have not fully mastered this technology, so its use is not optimal. This research uses a qualitative descriptive approach by utilizing a Technology Acceptance Model (TAM) based questionnaire to explore the perceptions of FKIP UMRAH students regarding the use of ChatGPT. The research results show that ChatGPT is widely accepted as an effective tool in completing academic assignments and increasing learning efficiency. However, challenges such as a lack of understanding of academic ethics, the risk of plagiarism, and over-reliance on technology are still problems. Educational institutions can increase digital literacy through special training and implementing stricter regulations regarding the use of AI. These findings make an important contribution to the literature on the acceptance of AI in education and offer practical solutions for policy use of learning technologies such as ChatGPT. Future research is expected to expand the sample scope and explore the long-term impact of AI on students' critical thinking abilities.